2014
DOI: 10.1371/journal.pgen.1004775
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Evidence of Rapid and Stable Adaptive Oscillations over Seasonal Time Scales in Drosophila

Abstract: In many species, genomic data have revealed pervasive adaptive evolution indicated by the fixation of beneficial alleles. However, when selection pressures are highly variable along a species' range or through time adaptive alleles may persist at intermediate frequencies for long periods. So called “balanced polymorphisms” have long been understood to be an important component of standing genetic variation, yet direct evidence of the strength of balancing selection and the stability and prevalence of balanced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
838
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 497 publications
(889 citation statements)
references
References 136 publications
43
838
7
1
Order By: Relevance
“…The fixation probability is also higher if the environmental changes are slower. year (10 generations) (2). Although the oscillations in many of these SNPs are likely driven by linkage to other seasonally selected sites, these data suggest that there are at least some driver alleles with sτ ≈ 1.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The fixation probability is also higher if the environmental changes are slower. year (10 generations) (2). Although the oscillations in many of these SNPs are likely driven by linkage to other seasonally selected sites, these data suggest that there are at least some driver alleles with sτ ≈ 1.…”
Section: Discussionmentioning
confidence: 82%
“…For example, drug resistance mutations often carry a cost when the dosage of the drug decays (1), and seasonal variations in climate can differentially select for certain alleles in the summer or winter (2). Similarly, laboratory adaptation to specific temperatures (3,4) or particular nutrient sources (5,6) often leads to declines in fitness in other conditions.…”
mentioning
confidence: 99%
“…This is because both sexes share many metabolic traits which are under selection to optimize contrasting reproductive demands between the sexes. Alternatively, both epistatic (He, Qian, Wang, Li, & Zhang, 2010; Jakubowska & Korona, 2012; Jasnos & Korona, 2007) and/or balancing selection via temporal variation in environmental conditions (Bergland, Behrman, O'Brien, Schmidt, & Petrov, 2014) could also be mechanisms to maintain genetic variance. One study has found season‐dependent oscillating patterns of allele frequency change of central metabolic and nutrient sensing genes (Cogni et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Species that we intend to kill tend to have very large population sizes and short generation times (e.g., insects, weeds, bacteria, viruses), and those species that we care about conserving tend to be larger bodied animals with relatively small population sizes and long generation times (e.g., most vertebrates). Short generation times allow evolutionary change to closely track the pace of environmental change (see, e.g., Bergland, Behrman, O'Brien, Schmidt, Petrov, 2014), thus minimizing the mismatch between physiological tolerance and the degree of environmental change. Large population sizes are important to buffer a species from stochastic extinction following rapid population decline in response to abrupt environmental change (Bell & Gonzalez, 2009).…”
Section: Natural Selection and Adaptive Responses To Rapidly Changingmentioning
confidence: 99%